158 Non-epithelial ovarian tumors: A single institute retrospective study. (13th November 2020) - de Sá, I; Raposo, S; Sousa, R; Sá, L
Abstract : Introduction: Non-epithelial ovarian tumors (NEOT) account for 10% of ovarian cancers. They occur in all age groups and include diverse tumors of germ cell origin, sex cord-stromal cell origin, as well as extremely rare types of ovarian cancer. The etiology and molecular origins of each sub-group remain poorly understood. Our aim is to determine the clinical, epidemiologic and histological features of the NEOT. Methods: A retrospective coorte study involving 33 patients diagnosed with NEOT and treated at IPO-Coimbra between 2011–2015. Patients 'data were obtained from hospital records. Results: The average age was 56 years. 42.4% of the patients were pre menopausal. We diagnosed 11 germ cell tumors (9 mature cystic teratomas, 1 mature teratoma and 1 immature teratoma), 21 sex cord-stromal tumors (16 ovarian fibromas/thecomas, 3 adult granulosa cell tumors, 1 juvenile granulosa cell tumor and 1 Sertoli-Leydig cell tumor) and 1 small cell carcinoma hypercalcaemic type tumor. All patients had surgery as a primary treatment; in 18.2% of the cases was performed a conservative surgery. Only 9.1% of patients were diagnosed in a stage > IA (FIGO). 2 patients were subjected to adjuvant chemotherapy (Sertoli-Leydig cell tumor and immature teratoma). After a mean follow up of 2.2 years, we reported 3 cases of relapse. 3 patients died between 2011–2015, but only one due the disease. The overall survival at 5 years was 97%. Conclusions: Our study reveals that the overall prognosis of NEOT is good. Relapse cases were mainly related to FIGO stage and more rare histologic type of tumor.